How Product Quality and Safety Drive Wardah Skincare Purchase Intention: The Moderating Role of Influencers - Yuhaniza Nahdhiyah; Pahrudin Pahrudin; Rohaeniyah Zain (LP2M IAIN Palopo, 2026)
We investigate whether product quality and product safety shape the intention to buy Wardah skincare. This study also tests if influencers can strengthen that link. This study involved 100 Wardah skincare users recruited via purposive sampling technique. Data were collected using a 5-point Likert scale questionnaire and analyzed with PLS-SEM. The results reveal that perceptions of product quality and safety have a significant positive impact on purchase intention. Surprisingly, the role of influencers did not significantly moderate the relationship between product quality, safety, and purchase intention. This indicates that consumers prioritize functional value and safety assurance over promotional figures. The key takeaway for brands: invest in better formulation and clear safety certification first. Use influencers mainly to educate customers about ingredients, not just for endorsements. Future work could add brand trust or perceived risk and reach a wider sample. Practically, marketing budgets should prioritize product R&D and BPOM certification over paid influencer posts.